RELEVANSI PEMBELAJARAN IPA DAN PAI HUMANIS - Subyanto; Kurniyatul Faizah (Fakultas Tarbiyah, Universitas Ibrahimy, 2019)
In Natural Sciences (IPA) there are three aspects of learning, they arenatural sciences as product, process, and strengthening attitudes. This natural sciences learning classification found relevance with Islamic education learning in the aspect of fiqh, theseare fiqh as a product and fiqh as a process. The types of humanistlearning arelearning other than as a product, because this learning is not just transfer of knowledge without rationality, so that the lesson is not able to take part in the real life of humanity. In the implementation, humanist learning can be carried out using several scientific approaches such as problem based learning, discovery learning, social interaction, role playing, team research, and other forms that are oriented to students involvementdirectly.